Peculiarities of Nervous System Properties Manifestation and Volition in Persons with Different Kinds of Addictive Behavior - A V Smirnov (Peoples' Friendship University of Russia (RUDN University), 2013)
The article presents the results of the empirical studies of the manifestations of nervous system properties and the will of persons with different types of addictive behavior. The results of the study suggest the similarity of these symptoms in the vast majority of addicts, regardless of the form of addiction, and their differences in individuals without addictions.